Effect of para-net shade level on plant microenvironment, growth, and yield of three strawberry varieties (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Suminarti NE, Sebayang HT, Maghfoer MD, Bulan. 2023. Effect of para-net shade level on plant microenvironment, growth, and yield of three strawberry varieties. Biodiversitas 24: 2149-2155. Plant environmental management through the application of para-net shade and the selection of adaptive varieties for strawberry plants has been carried out from March to June 2020 in Jatikerto.The study used a split-plotdesign by placing shade treatments on the main plot consisting of four types, namely without shade (0%), 25% shading, 50% shading, and 75% shading, while the variety treatment was placed in subplots consisting of three kinds, namely Sweet Charlie, California, and Earlibrite varieties.The 5% F test was used to determine the interaction or significant effect of the treatments, while the 5% HSD test was used to determine differences between treatments.The results showed that there was a significant interaction in observing fruit weight per hectare. In the treatment without shade and with 25% shade, the highest fruit weight was produced by the California variety, 1.06 t ha-1,and 0.80 t ha-1, respectively. Whereas at 50% shade, the highest fruit weight per hectare was found in the Sweet Charlie variety, namely 0.66 t ha-1, and at 75% shade, higher yields were found in the Sweet Charlie and Earlibrite varieties, each of 0.65 t ha-1and 0.55 t ha1. Conclusion: California is a fairly tolerant variety to be developed in the Jatikerto area.